One Ferroptosis-Related Gene-Pair Signature Serves as an Original Prognostic Biomarker in Lung Adenocarcinoma - Li, Lei; Wang, Buhai (Frontiers in Genetics, 2022)
Lung adenocarcinoma is the most common histological subtype of lung cancer which induces the largest number of deaths worldwide. Depending on the illustration of tumorigenesis, exploring reliable prognostic biomarkers based on biological behaviors and molecular mechanisms is essential for detecting prognosis and individualized treatment strategies. Ferroptosis is a newly found type of regulated cell death and associated with harmful lipid peroxidation in cells. We collected ferroptosis-related genes and transcriptome profiles of Lung adenocarcinoma from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) to construct ferroptosis-related gene-pair matrixes. Then we performed the least absolute shrinkage and selection operator regression to build prognostic ferroptosis-related gene-pair index (FRGPI) in the TCGA training matrix. Our study validated FRGPI through ROC curves, Kaplan-Meier methods, Univariate and multivariate cox hazard analyses in TCGA and GEO cohorts. The optimal cut-off 0.081 stratified patients into low and high FRGPI groups. And the low FRGPI group had a significantly better prognosis than the high FRGPI group. For further study, we chosen SLC7A11 and MKI67 which significantly up-regulated in the high FRGPI group, whereas GLS2 down-regulating in the high FRGPI group. Gene set enrichment analysis (GSEA) enrichment maps indicated that cell cycle, DNA replication, proteasome, and p53 signaling pathway significantly enriched in the high FRGPI group. The high FRGPI group also presented higher macrophage M1 infiltration. Meanwhile, there were few differences of adaptive immune responses between high and low FRGPI groups. In conclusion, FRGPI, as an independent prognostic biomarker, stratified patients into two groups with different outcomes and guided us to activate ferroptosis during conventional cancer therapy for a better prognosis, especially in the high FRGPI group.